Capacidade governativa e desenvolvimento socioeconômico: o caso do Acre e Rondônia - Oliveira, Marcílio Lima de (2021)
The new development alternatives based on local values in Brazil is an extremely important theme in the current socioeconomic context of the Brazilian Amazon. The geographical scope of this research comprises the Immediate Geographic Regions of IBGE and their respective regional hubs located in the states of Acre and Rondônia. In these spatialities, the accommodation of the interests of the economic and political elites with those of the local communities does not always converge. This makes development in these territories a slow process until new initiatives and alternatives become effective for each place. In this environment, the possibilities for development would pass through the expansion of the governing capacity of the public sector, local initiatives, and the organizational capacity of regional agents. This conjuncture is the root of the persistence of challenges that characterize these states as traditional spaces of socioeconomic inequality. The general objective of this thesis is to comparatively analyze by means of two new indexes, Government Capacity Index (ICG) and Socioeconomic Development Index (IDSE), the public management capacity and the level of socioeconomic development, between the years 2000 and 2018. To achieve the proposed objectives, 58 variables were used, typified as qualitative and quantitative simple count, to characterize the two development models, one based on an exogenous vision of territory and the other, on an endogenous vision. Using the Deplhi method, local initiatives and organizational capacity were evaluated in relation to the regional actors' perception of the results of the two proposed indexes. The contributions of the analysis of the governing capacities suggest that the low degree of participation of society in the decision-making arenas of public policy formulation derives from the inexistence of management and planning instruments, a factor that may have influenced the deepening of social inequalities in most of the immediate regions of Acre and Rondônia. As to the main results, it was concluded that in Rondônia, the size of its consumer market and its geographical position contributed to a viable alternative resulting from the agricultural economic cycle, and with this it started to direct the productive process towards exportation, as an economic viability for the state. In the case of Acre, the bias of environmental sustainability, as an institutional guideline, strongly affected the economic result of the agricultural system that helped it to strengthen the dependence on the returns from the FPM (Municipal Participation Fund). The regions of Vilhena (RO) and Brasiléia (AC) are appropriate to exemplify relevant aspects of the endogenous manifestation and rationality on which the governance system constituted added positive effects on their development. The fieldwork revealed that in Rondônia, collective organizations, due to their disarticulations are not recognized as an instrument for the promotion of regional development. In Acre, the inherited social and economic conditions allowed the formation of a collective social organization in favor of development (Forum of Regional Development), which encompasses public agents and private agents that seek to build an agenda of change based on local values. It also became evident that the alternatives envisioned for development are plausible as long as they advance in the sense of aggregating local values.